20p12.3 deletion is rare cause of syndromic cleft palate: case report and review of literature. (December 2016) - Amasdl, Saadia; Natiq, Abdelhafid; Sbiti, Aziza; Zerkaoui, Maria; Lyahyai, Jaber; Amzazi, Saaid; Liehr, Thomas; Sefiani, Abdelaziz
Abstract Background Orofacial cleft (OFC) is one of the most common congenital malformations with a global incidence of approximately 1/700 live births. Clinically, OFCs can be syndromic or non-syndromic. Case presentation A 5 years old boy admitted for genetic evaluation because of psychomotor delay, failure to thrive, dysmorphic features and cleft palate. Conventional cytogenetic showed a notably short p arm of one chromosome 20. FISH analysis identified the derivative chromosome 20 as a de novo 20p12.3 deletion. Conclusion We present in this paper a Moroccan patient with syndromic cleft palate caused by a de novo 20p12.3 deletion, and we highlight the interest of FISH in the diagnosis confirmation of chromosomal rearrangement. In practice, 20p12.3 deletion should be considered as an etiological diagnosis in the case of syndromic cleft palate.